Motivating Generation Z — the volunteers of the future - Henrik Pahus; Tina Knuth (Research in Hospitality Management, 2023)
In this article, we present the results of an ongoing research project from 2020 to 2023 on volunteerism and Generation Z. The purpose of the overall project is to examine which elements are motivating or demotivating to volunteers from Generation Z in the hospitality sector. We present the analysis of 12 interviews with leaders of volunteers and the results of a survey with 514 volunteers from Denmark. Our findings show a generation that are much more reliant on their parents than previous generations, especially in the way they make decisions. It is also a generation with endless opportunities, which seems to be a double-edged sword, since this is also the root cause of many of their concerns. Companies in the hospitality sector who are keen to attract volunteers from Generation Z must pay attention to their inherent needs for meaningfulness and purpose. Likewise, it is essential that the companies where Generation Z seek employment are clear about their values and that the abide by them. Suggestions for further research include more comprehensive research into attitudes towards volunteerism — especially considering the cultural context. So far most of the research concerning volunteerism and motivation in Generation Z stems from the USA and Denmark.